Petrogenesis and tectonic implications of the Early Jurassic syenogranite in the northern section of Zhangguangcai Range, NE China: insights from geochronology, geochemistry, and Lu-Hf isotopes - Liu, Liye; Duan, Mingxin; Huang, Jimin; Song, Haonan; Lin, Xiangpeng; Zhan, Yong (Frontiers in Earth Science, 2025)
The Lesser Xing’an-Zhangguangcai Range tectonic belt in northeastern China is located along the eastern margin of the Central Asian Orogenic Belt and serves as the key to understanding the tectonic transition between the Paleo-Asian Ocean and Paleo-Pacific regimes during the Early Mesozoic. This study presented the zircon U-Pb geochronology, Hf isotope, and whole-rock geochemistry of Early Jurassic syenogranites from the northern Zhangguangcailing Range. The LA-ICP-MS zircon dating result indicates a crystallization age of 194 ± 2 Ma. Integrated with regional data, this study confirmed that the Early Mesozoic magmatism in the region was concentrated in the Early Jurassic (180–200 Ma). The granites displayed typical arc-related features, including (1) high SiO2 (70.59–76.81 wt.%), alkali enrichment (Na2O + K2O = 7.65–8.38 wt.%), low Mg and Fe contents, classifying them as the high-K calc-alkaline metaluminous to weakly peraluminous (A/CNK = 0.99–1.04); (2) strong LREE enrichment with weak Eu anomalies (δEu = 0.44–0.81) and HREE depletion ((La/Yb)N = 3.38–16.17); and (3) enrichment in LILEs (Rb, K) with the corresponding depletion in HFSEs (Nb, Ta, and Ti). Harker diagrams showed negative correlations between SiO2 and MgO, TiO2, CaO, TFeO, P2O5, and Eu, indicating fractional crystallization involving amphibole, ilmenite, apatite, and feldspar. The zircon εHf(t) values (+2.7 to +5.0) and the corresponding Meso-to Neoproterozoic crustal model ages (TDM2 = 915–1067 Ma) suggested that the magma originated from partial melting of the Meso-Neoproterozoic mafic lower crust at amphibolite facies. The geochemical and isotopic data collectively identified these rocks as I-type granite. In a regional tectonic context, their formation was interpreted to reflect an active continental margin environment driven by the westward subduction of the Paleo-Pacific Plate during the Early Jurassic, potentially influenced by the closure of the Mudanjiang Ocean, a branch of the Paleo-Pacific.